INTEGRATION OF ISLAMIC ECONOMICS IN THE IMPLEMENTATION OF GREEN SMART CITY IN THE SPECIAL REGION OF JAKARTA - Nur, Syafri Muhammad (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to analyze the integration of Islamic economic principles in the implementation of a green smart city in the Special Capital Region of Jakarta. The focus of the research is directed at how sustainability, efficiency, and justice embedded in Islamic economics can support technology-based and environmentally friendly urban governance. This study employs a qualitative method with a literature review and thematic analysis of government policies, smart city practices, and previous studies from the last five years. The results show that implementing a Sharia-based green smart city can strengthen public financial governance, enhance community digital literacy, and support strategic sectors such as renewable energy, zakat management, and sustainable financing. The discussion highlights that although opportunities are significant, challenges remain in regulation, technological gaps, and multi-stakeholder coordination. The conclusion emphasizes that integrating Islamic economics into the green smart city model in Jakarta has the potential to create more inclusive, fair, and sustainable urban governance, while also serving as a modern Islamic city development model.